USING MOBILE APPLICATIONS TO IMPROVE LANGUAGE LEARNING AMONG EFL STUDENTS (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This paper explores how mobile applications enhance English as a Foreign Language (EFL) learning through personalized, accessible, and gamified experiences. Drawing on empirical studies and real-world app-based implementations, the study examines how features like AI feedback, gamification, and adaptive learning algorithms contribute to improved motivation and skill development. Findings indicate that mobile apps significantly impact learners' autonomy, pronunciation, and speaking fluency when properly utilized within supportive learning frameworks.